(3JObjb GdHfhc hGdCOhGJ GdeGdjI GdeTJbI (B:s (3habG dCMOK GdHjGfGJ GdOhdjI deeGQSI GdJObjb (B/s - (3LeYI, CMeO Mdejs ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2013)
(3GdJNWjW dJObjb GdHjGfGJ GdeGdjI ddHfhc(B- (3JMOjO hJbjje eNGWQ GdCNWGA GdLhgQjI YfO JObjb GdHjGfGJ GdeGdjI ddHfhc(B- (3COdI hfJGFL JObjb GdHjGfGJ GdeGdjI ddHfhc(B- (3GdYdGbI Hjf GdeObjbjf GdNGQLjjf heTQaj GdHfhc(B- (3JObjb GdCOhGJ GdeGdjI GdeTJbIs
(3GdedGMb U(B.301(3; GdeQGLY U(B.323s
Keywords: (3GdHfhcs; (3JObjb GdMSGHGJs